Cytomegalovirus Infection in Infants: Course Variants, Modern Approaches to Therapy (Clinical Cases) - Irina A. Belyaeva; Elena P. Bombardirova; Tatiana V. Potekhina; Aleksandra S. Gurskaya (Union of pediatricians of Russia, 2018)
Cytomegalovirus infection (CMVI) in newborns and infants can occur in various clinical forms requiring a differentiated therapy. We present the peculiarities of two different variants of CMVI course generalized with a manifest clinical picture and characteristic shifts in laboratory analyzes in a child aged 2.5 months with a combined genetic pathology, and latent intrauterine in a child aged 5 days leading to the development of neurosensory hearing loss. The difficulties in diagnosing a suppressed (latent) form of the disease and choosing a therapeutic approach have been highlighted. A successful result of etiopathogenetic therapy with ganciclovir in a child with postnatal generalized CMVI has been presented. The therapeutic efficacy and safety of off-label ganciclovir preparations and anti-cytomegalovirus immunoglobulin have been confirmed. The advisability of including ganciclovir in the management protocol of children with latent forms of CMVI is discussed.